Do porco não sobra nem o grito!: classificações e práticas, saberes e sabores no abate doméstico de porcos - Froehlich, Graciela (2012)
This dissertation is based on fieldwork developed among settlers in the city of São Paulo das Missões, RS. It was pursued, through field insertions, to analyze the process of domestic slaughter, locally called as carneada, focusing on the feeding goal that guides the carneadas as starting-point of this reflection. The discussion‟s center line is feeding, taken from the cultural point of view, in other words, a process that is not only biological, but eminently symbolic. From this idea, knowledge and practice that guides the carneadas are valued, in a way which these distinguish themselves from others forms of animal death with feeding purposes, such as sacrifices and industrial slaughter. In classification and preferences that orientate the selection of the animals, as well as the caring in the animal breeding feeding and health care it can be said that it is when begins the transmutation from animal to food, that continues to the slaughter itself. The carneadas are described from the experience lived in the field, where it was aimed to highlight aspects, such as reciprocity, labor and sexual division, also, it is bounced the festive and mnemonic features. Through the dialogues established in the field, it is aimed to capture how this practice modified itself through the years and the impacts of these changes in the family‟s feeding habits and sociability that I have made contact.